The comparison of homogenous and heterogenous group in applying jigsaw method - Dewanti, Septinda Rima (Universitas Negeri Yogyakarta, 2020)
Jigsaw is a kind of cooperative learning methods. This method has been known as an effective method in schools either for junior or college students. This study aims to describe the differences between two groups, that are one group formed based on gender, ability, ethnic and another group formed as a homogenous. Both of groups were applying jigsaw method in educational psychology course. The research method was comparative design. The subject of this study are all students who enrolled in educational psychology course. The result of this study is the effectivity of both groups formed in the jigsaw method has no significant difference. So, to conclude this research, teachers in schools should more concern in group dynamic than the component of groupsjigsaw, heterogenous and homogenous group